Mixed Dicarboxylic Acids Derived from Polyethylene as a Feedstock for the Synthesis of Polyesters - Smak, Tom J; Aalders, Hugo; van Bruggen, Rijk; Out, Thijs; van Rijn, Bram; Ruijs, Carmen; Altink, Rinke; Vollmer, Ina; Weckhuysen, Bert M (ACS sustainable chemistry & engineering, 2025)
To move away from the currently linear fossil-based plastic value chain, we aim to produce dicarboxylic acid monomers, such as succinic and adipic acid, by the oxidative conversion of polyethylene (PE) wastes. However, a drawback of this technology is that a mixture of dicarboxylic acids of various chain lengths is produced, in contrast to their fossil-based analogs. Therefore, we aim to explore the potential of applying mixed dicarboxylic acids directly in polyester synthesis. The physical properties of these polymers were compared by synthesizing a range of aliphatic polyesters from dicarboxylic acids with a variation in chain length (i.e., C4-C10) and chain length distributions (i.e., 1, 3, 5, and 7 diacids) with 1,4-butanediol as the comonomer. In addition, a polyester was synthesized from a mix of dicarboxylic acids derived from the oxidative conversion of polyethylene (PE). The polymers were characterized with differential scanning calorimetry (DSC), gel permeation chromatography (GPC), X-ray diffraction (XRD), infrared (IR) spectroscopy, nuclear magnetic resonance (NMR), and thermogravimetric analysis (TGA). Using a mixed dicarboxylic acid feedstock enhances the biodegradability but lowers the melting temperature of the polymers made. This can be compensated by the use of a more rigid diol, such as bis-hydroxyethyl terephthalate (BHET).